Analisis Kaidah Tasharruf Al-Imam ‘Ala Al-Ra’iyyah Manuthun Bil Maslahah dalam Perspektif Qowaidh Fiqh Siyasah - Muh. Zamroni; Riza Aulia Rahmanita; Alyada Esa Az Zahra; Fajar Wahyu Hasana (STIKes Ibnu Sina Ajibarang, 2026)
The fiqh principle stating that a leader’s policies and actions toward the people must be based on public welfare is an Islamic legal principle emphasizing that every action and policy of a leader should be oriented toward the interests and well-being of society. This study aims to examine the meaning, normative foundations, concepts, and implementation of this principle in state governance. The research employs a library research method with a normative approach through the analysis of the Qur’an, Hadith, fiqh literature, scholarly journals, and relevant legislation. The findings indicate that this principle has a strong foundation in the Qur’an and Hadith, particularly regarding trustworthiness, justice, and the responsibility of leaders toward their people. Conceptually, this principle is closely related to the theories of maqashid al-shari’ah and siyasah shar’iyyah, which place public welfare as the primary objective of Islamic law. In practice, the principle is applied in various fields, including public administration, law and legislation, religious policies, as well as economic and fiscal policies. Its implementation can be seen in policies concerning the prohibition of interfaith marriage, marriage dispensation, marriage legalization hearings (isbat), the suspension of Hajj departures during the COVID-19 pandemic, and the management of state finances during the era of the Rightly Guided Caliphs. Therefore, this principle demonstrates that Islamic law possesses flexible and adaptive characteristics while maintaining a strong orientation toward public welfare, making it relevant to modern systems of governance.